(untitled) (Construction Economics and Building, 2020)
The urban public housing project, especially for low-income people, is essential to cater to the increasing urbanisation rate in Malaysia. This study aimed to gain an understanding of the project governance practices in urban public housing projects in Malaysia, which will lead to better project delivery and the successful outcome of the projects. A single case study was conducted on a public housing project or known as Projek Perumahan Rakyat (PPR) in Kuala Lumpur, and data for this study was gathered using semi-structured interviews with six (6) public officials, document analysis, and observation. The findings of this study indicate the positive interplay between project actors guided by the elements of trust, stakeholder management, empowerment, and collective decision making, which create value for the project. Hence, this article contributes to the dynamic understanding of how public officials practice project governance in conducting their works related to urban public housing projects. The findings of the study will enable related public organisations to reinforce the underlying project governance elements towards the strengthening of urban public housing delivery system. Case study research in different models of urban public housing could extend the discovery of other project governance elements while validating the findings of this study from different perspectives. The findings of the study are limited due to the use of a single case study related to the urban public housing project and its contexts.